2023
DOI: 10.3897/pharmacia.70.e105126
|View full text |Cite
|
Sign up to set email alerts
|

Non inferiority trial of Channa striata extract on endothelial glycocalyx layer protection in septic patient: a prospective cohort study

Septian Adi Permana,
Hartono Hartono,
Bambang Purwanto
et al.

Abstract: Introduction: Sepsis causes significant damage to the endothelial glycocalyx layer, which albumin can protect against. Unfortunately, human albumin is quite expensive, so cheaper substitutes must be found without sacrificing effectiveness. Albumin extract Channa striata is one that is commonly used in Indonesia. Objectives: Conducted a non-inferiority study between human albumin and Channa striata extract in protecting the glycocalyx layer through syndecan-1 levels. Materials and methods: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Meanwhile, the use of CS extract in other critical diseases (e.g., stroke) may increase albumin levels after CS supplementation (Kasim et al, 2017). In this study, patients with sepsis received CS supplements for five days (Permana et al, 2023). In another study, five-day CS supplementation accelerated healing processes and wound inflammation after the surgery.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Meanwhile, the use of CS extract in other critical diseases (e.g., stroke) may increase albumin levels after CS supplementation (Kasim et al, 2017). In this study, patients with sepsis received CS supplements for five days (Permana et al, 2023). In another study, five-day CS supplementation accelerated healing processes and wound inflammation after the surgery.…”
Section: Discussionmentioning
confidence: 86%
“…It turned out that there was no significant difference between the two in stabilizing PAI-1 in sepsis patients (p = 0,503). In addition, platelet differences between the CS group and human albumin were not significant differences (p = 0.187) (Permana et al, 2023) then conducted a follow-up study in 2023 with the same treatment group with administration for two days to see the effect on syndecan-1. It was found that there was a decrease in syndecan-1 in the CS group (p = 0.013) and human albumin (p = 0.027), so it was concluded that there was no significant difference between the two.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation